Metode Pendidikan Perspektif Mufassir Quraish Syihab (Talaah Surat Al Maidah Ayat : 67, An Nahl Aayat : 125) - Hermanto, Su'ud; Azizah, Zidna Nur; Nihayah, Hamidatun (STAINU Purworejo, 2023)
Education is a conscious effort to explore and develop human abilities with the aim of changing established knowledge, behavior and norms. Islamic education is different from other education because it looks at good and bad things comprehensively. Islamic education must be based on the Koran, which functions as the main source of law for the Islamic religion. Islamic education must also be based on hadith. In the end, people who have abilities in educational aspects that are in line with the two main sources of law will be produced. Therefore, all efforts must be in accordance with the demands of the Koran and Hadith, not just changing behavior or ways of thinking. Education and teaching activities can only be successful if they have good elements.